Serum amyloid A (SAA) variations in patients with cancer: correlation with disease activity, stage, primary site, and prognosis. Issue 7 (July 1986) - Biran, H; Friedman, N; Neumann, L; Pras, M; Shainkin-Kestenbaum, R
Abstract : Serum amyloid A (SAA) was determined in 160 patients with cancer. Active disease was associated with high titre compared with the titre in non-active condition (31.8 v 5.8 micrograms/ml, respectively; p = 0.0002). SAA value showed a direct correlation with the stage of the disease: it was lowest at stages 1 and 2 and highest at the metastatic stage 4 (stage 1 v 4, p = 0.001; stage 2 v 3, p = 0.05). Cancers of the lung and unknown primary site were characterised by highly increased SAA concentration. Initial SAA value had prognostic significance: a value below 10 micrograms/ml correlated with survival advantage, whereas a higher initial value indicated a greater likelihood of a poor outcome (actuarial survival analysis p less than 0.001). When stage was accounted for, initial SAA value had significant prognostic bearing on survival of patients with advanced disease (stages 3 and 4) but not on that of patients with limited disease (stages 1 and 2). Serial testing showed good concordance between changes in SAA titre and clinical course.